Investment Value Analysis of Internet Companies Based on the FCFF Model - Maolin, Hu (Advances in Social Sciences Research Journal, 2024)
With the continuous progress and development of society, China's capital market has experienced successive waves of investment enthusiasm. As investors’ perspectives become increasingly rational, companies' management objectives have shifted from an initial focus on profit maximization to a broader goal of maximizing corporate value. Throughout this evolution in management goals, investors have become more concerned with the intrinsic value of companies. With the advent of the 5G era, the internet industry is experiencing a new wave of development. Against this backdrop, how investors can reasonably assess the value of internet companies and capture their intrinsic investment value has become critically important. This paper evaluates the corporate value of Internet Company A based on the Free Cash Flow to Firm (FCFF) model, exploring the model's applicability in the internet industry and providing a reference for investors seeking to assess corporate value.